Substrate Dependent Microbial Bioremediation in Freshwater Marron (Cherax cainii Austin 2002) Aquaculture - Cole, Anthony J. (Curtin University, 2019)
A series of four experiments were conducted to investigate the role of an oil-based substrate to bioremediate water quality during marron aquaculture, and its effect on plankton communities, marron productivity and marron health. The selected substrate had varied effects in different culture environments in reducing concentrations of ammonia, nitrite, nitrate, and orthophosphate, provided a habitat for heterotrophic bacteria, including Bacillus sp., and had no detrimental effects on marron or plankton communities during marron aquaculture.